In(III)-TMSBr-Catalyzed Cascade Reaction of Diarylalkynes with Acrylates for the Synthesis of Aryldihydronaphthalene Derivatives - Zhang, Qiu-Chi (2018)
A combined Lewis acid system comprising of two or more Lewis acids occasionally exhibits augmented catalytic activity in organic transformations which are otherwise unrealizable by either of the components exclusively. On the other hand, the efficient construction of multiple new C-C bonds and polycyclic structures in minimal steps remains a subject of great interest in both academia and industry. Herein we report an efficient method to assemble aryldihydronaphthalene derivatives via a cascade reaction of diarylalkynes with acrylates under the catalysis of a combined Lewis acid derived from In(III) salt and TMSBr.